Pater Oton Škola in njegov rokopisni slovar Pronouncing Dictionary – English and German (1839) - Štavbar, Simona (Slavia Centralis, 2020)
Fr. Otto Skolla and his Manuscript Dictionary Pronouncing Dictionary – English and German (1839)The article discusses the manuscript dictionary Pronouncing Dictionary – English and German compiled by the Slovenian Franciscan missionary, lexicographer and painter, Fr. Otto Skolla. The dictionary from 1839 is to my knowledge the only preserved example of a pronouncing dictionary compiled by the Slovenian missionary, probably for his own use, i. e. to learn a foreign language (English) for the purpose of his missionary work. The dictionary has thus far not been discussed in more detail in Slovenian scholarly literature. The article offers a short presentation of the life and work of the Franciscan missionary Fr. Otto Skolla followed by the metalexicographic description and the description of certain microstructural characteristics of this dictionary.
Keywords: manuscript dictionary; pronouncing dictionary; missionary lexicography; metalexicographic description